THE EFFECT OF SPARK PLUG GROUND ELECTRODE ON SPARK IGNITION ENGINE PERFORMANCE - Zain Lillahulhaq; Rizal Mahmud; Safiullah Safiullah (Jurnal Rekayasa Mesin, 2022)
Motorcycle performance is influenced by many factors, including combustion chamber dimension, fuel characteristic, type of spark plug, spray flame, ignition timing, and the combustion chamber's cooling system to avoid incomplete combustion and knocking processes. The spark plug is an essential component of SIE. Several studies, such as spark plug gap, material type, multiple-ground Electrode, roughness, etc., have been conducted to examine the effect of spark plug modifications on the combustion process. Some previous research investigates the impact of a multiple-ground electrode spark plug in biofuel combustion. However, a study about the effect of multiple-ground electrode spark plugs on the gasoline combustion process has not been conducted. This research was conducted to determine the impact of multiple-ground electrode on Supra 125 cc performance. The data displayed in this study are power, torque, BHP, and BMEP in single, double, and triple ground electrode. The results showed that the double ground electrode spark plug produced better performance than other variations.